2021
DOI: 10.1111/1755-6724.14677
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Mafic Microgranular Enclaves in the Shaocunwu Granodiorite, Southern China, and their Implications: Evidence from Zircon and Whole‐rock Geochemistry

Abstract: Magmatic microgranular enclaves (MMEs) are widely developed in the Shaocunwu granodiorite at the northeast margin of the eastern Jiangnan orogenic belt. Field geology showed that the MMEs occur as irregular ellipsoids near the edge of the intrusion, and consist of diorite, dominantly composed of amphibole, biotite, and plagioclase grains, with minor acicular apatite. Zircon U‐Pb dating showed the ages of the host granodiorites and MMEs are 145.9 ± 1.1 Ma and 145.6 ± 2.5 Ma, respectively, indicating both origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…The calculated Ce/Nd ratios of zircon from the Mamupu QSP range from 4.3 to 34.7 (average 20.2), which is similar to the fertile Yulong (average 29.5) and Beiya porphyries (average 19.8) in the same belt (Bao et al, 2020), indicating that the Mamupu QSP has a high magmatic oxygen fugacity. Previous studies have shown that log(f O2 ) of zircons relates to their crystallization temperatures (Trail et al, 2011;Jiang et al, 2021) and zircons from the Mamupu QSP have a high zircon log(f O2 ) (averaging −13.5). In the zircon T (calculated from Ti-in-zircon thermometers, Ferry and Watson, 2007) vs. log(f O2 ) diagrams (Fig.…”
Section: Implications For Eocene Metallogenesis In the Ypcbmentioning
confidence: 99%
“…The calculated Ce/Nd ratios of zircon from the Mamupu QSP range from 4.3 to 34.7 (average 20.2), which is similar to the fertile Yulong (average 29.5) and Beiya porphyries (average 19.8) in the same belt (Bao et al, 2020), indicating that the Mamupu QSP has a high magmatic oxygen fugacity. Previous studies have shown that log(f O2 ) of zircons relates to their crystallization temperatures (Trail et al, 2011;Jiang et al, 2021) and zircons from the Mamupu QSP have a high zircon log(f O2 ) (averaging −13.5). In the zircon T (calculated from Ti-in-zircon thermometers, Ferry and Watson, 2007) vs. log(f O2 ) diagrams (Fig.…”
Section: Implications For Eocene Metallogenesis In the Ypcbmentioning
confidence: 99%